Alzheimer's Disease Warning Signs: Gender and Education Influence Modifiable Risk Factors—A Pilot Survey Study. (3rd October 2021) - Parker, Kelly; Rhee, Yeong
Abstract: Objective: The aim of this research was to determine the relationships among diabetes, Alzheimer's disease warning signs, and lifestyle factors such as fruit and vegetable intake and physical activity. Method: Adults over the age of 50 (N = 147) responded to a survey about their health, family history, and experience of Alzheimer's warning signs in the previous year. Results: Pearson's correlation revealed significant relationships between fruit and vegetable intake and education, gender, and physical activity. Alzheimer's warning signs were associated with relatives having an Alzheimer's disease diagnosis. Other results were nonsignificant. Conclusions: Diabetes impacts one-third of older adults in the United States and increases the risk of Alzheimer's disease. This survey revealed that women, who are more at risk for Alzheimer's disease, are less likely to engage in physical activity, a behavior that could decrease their risk. Similarly, those with higher education were more likely to consume colorful fruits and vegetables, potentially decreasing their risk of Alzheimer's disease.